RELATIONSHIP HUSBAND’S SUPPORT WITH NUTRITIONAL STATUS OF INJECTABLE CONTRACEPTIVES ACCEPTOR - Ambarwati, Nining; Armini, Ni Ketut Alit; Krisnana, Ilya (University of Muhammadiyah Malang, 2019)
Hormonal contraception type injectable contraceptives increasingly popular in Indonesia because of its practical, cost-effective, and safe. Side effects of use injectable contraceptives is changes in nutritional status. Nutritional status is a measure in the assessment of nutritional fulfillment that reflects a person's health status. Changes in nutritional status are multifactorial like husband’s support. This study aims to explain the relationship between husband’s support with nutritional status on injectable contraceptives acceptor. This study used cross sectional design. The sample in this research is women of childbearing age who use injectable contraceptive of Puskesmas Gading Surabaya region obtained by purposive sampling technique. Independent variable is husband’s support. The dependent variable is the nutritional status of injectable contraceptives acceptor. The instruments in this study were questionnaires and BMI measurements. To find out the relationship, this study uses Spearman correlation test. Husband’s support with nutritional status on injectable contraceptives acceptor, obtained result p = 0,00 (r) = -0,546. The husband’s support with nutritional status on injectable contraceptives acceptor has a moderate correlation with negative correlation coefficient, it means that less respondents get support from their husbands, nutritional status will increase until they get overweight or obese. It is necessary to increase the involvement of husbands in deciding the use of contraception, so women of childbearing age of injecting contraceptives acceptor receives adequate husband’s support.